Screening of alkali‐assisted storage conditions to define the operational window of deacetylation within storage systems in the bioenergy supply chain. (16th September 2021) - Wendt, Lynn M.; Wahlen, Bradley D.; Walton, Michelle R.; Nguyen, Jason A.; Lin, Yingqian; Brown, Rebecca M.
Abstract: Overcoming biomass heterogeneity and associated recalcitrance to thermal, chemical, and enzymatic depolymerization is a necessary but challenging aspect of valorizing lignocellulosic biomass to fuels and chemicals. This study explores how this recalcitrance can be reduced during the supply chain unit operation of storage, which is required for seasonally harvested agricultural residues to maintain constant throughput at a biorefinery. In this work, partial alkali pretreatment was performed just prior to corn stover entering storage, which had the benefit of providing a high pH environment entering storage such that soluble sugars were preserved and saponified acetyl groups in hemicellulose. This work investigated a range of viable conditions where saponification and preservation occur simultaneously by varying the moisture content (40% and 60%) and concentrations of sodium hydroxide (low and high) during aerobic and anaerobic storage. Anaerobic conditions preserved overall dry matter below 5% in the three scenarios evaluated, and the highest alkali loading solubilized up to 15% lignin, 18% xylan, and 50% of acetate, meanwhile doubling the extractable components. Scanning electron microscopy images highlighted potential physical impacts including cell‐wall disruption near vascular bundles, pitting within parenchyma cells, and cell‐wall distortion. Techno‐economic assessment indicated that this storage approach and associated logistics system is economically competitive with a conventional approach using low‐moisture bales. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd